DEPENDENCE OF EXTERNAL AND INTERNAL ENERGY-SAVING FOR RECTIFICATION OF BINARY MIXTURES - M. K. Zakharov; A. A. Shvets (Тонкие химические технологии)
The comparison of energy consumption for rectification of binary mixtures in one-column and twocolumn apparatuses was carried out with the use of vapor flow energy from the first column for heating the second column. It is shown that the expected two-fold reduction of the flow of heat energy is impossible due to the decrease of the internal energy-saving.